1981
DOI: 10.3109/00048678109159423
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Summer Camps 1979 — Problems of Measuring Behaviour Change in Children

Abstract: To develop experience in assessing behaviour change in children, sixteen children attending week-long summer camps run by the Department of Psychiatry, Adelaide Children's Hospital in January 1979, were assessed every two months for six months. Target complaints, symptom checklists and measures of social behaviour were chosen as being most likely to be sensitive to behaviour change. Hypotheses about the summer camp experience having an influence on severity of target behaviour problems, symptoms indicating chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Battle and associates (1966) reported that both methods were reliable, but no reliability data were provided. Gerrard and Heins (1981) found the TC to be a valuable tool for the assessment of behavioural changes in children. They did not comment on any other aspects of its clinical utility.…”
Section: Target Complaints (Tc)mentioning
confidence: 99%
“…Battle and associates (1966) reported that both methods were reliable, but no reliability data were provided. Gerrard and Heins (1981) found the TC to be a valuable tool for the assessment of behavioural changes in children. They did not comment on any other aspects of its clinical utility.…”
Section: Target Complaints (Tc)mentioning
confidence: 99%